A COMPARATIVE APPROACH TO UNDERSTANDING BACTERIAL PATHOGENICITY: THE ROLE OF ENZYMATIC AND HEMOLYTIC VIRULENCE FACTORS - Suleiman, Raghad Z. (Journal of Medical Genetics and Clinical Biology, 2024)
This comparison study has aimed to identify the impact of enzymatic and hematogenic virulence factors on the pathogenesis of bacteria using S. aureus (ATCC BAA-976) and E. coli (strain O157) as examples. Protease and lipase activity levels were measured using enzyme tests; the hemolytic activity was measured by examining the growth of the bacteria, with non-hemolytic colonies producing a zone around them. A two-tailed t-test was used to build this statistical relationship. The results showed that S. aureus and E. coli had significantly different levels of enzyme activity. Protease and lipase activity levels were higher in S. aureus than in E. coli. It also revealed significant differences in hemolysis zone widths between the two strains, with S. aureus having a greater hemolysis zone diameter than E. coli. Hemolytic virulence factors are crucial for bacterial pathogenic action, allowing them to thrive within host tissues, gain nutrition from red blood cells, and evade the host's defense mechanism. This study can help develop targeted strategies for fighting infections and improving patient outcomes during infection transmission